Labor markets - Andrzej Klimczuk (The Wiley-Blackwell Encyclopedia of Social Theory, 2017)
In a market economy, human work is offered and sought in the labor market. It is valued because of the level of demand for it and the rarity of the required qualifications. At the same time, because of the different contexts and conditions, there are many labor markets that are defined as the professional labor markets, local labor markets, dual labor markets, and black and gray labor markets.
Keywords: J21; 330; discrimination; employment; dual economy